A major plant practice at the Philippine Carabao Center at the University of the Philippines Los Baños, Laguna - Dimaano, Exequiel Pabonita (2007)
The proponent has his internship at the Philippine Carabao Center (PCC) at UPLB from April 23 to May 23, 2006. As a government agency advancing the economic use of the buffalo milk, PCC manufactures sterilized fresh milk, chocolate milk, yoghurt, kesong puti and pastillas de leche. During the internship, the proponent was exposed to different production areas, which included the raw milk production area; sterilized fresh milk and chocolate milk production area; and yoghurt, kesong puti and pastillas de leche production area. In the raw milk production area, he experienced daily collection of milk from dairy buffalo and transportation of the collected raw milk to designated processing areas. At the Dairy Training and Research Institute where sterilized fresh milk and chocolate milk are produced, he was able to experience continuous processing of milk. He also experienced batch processing of yoghurt, kesong puti and pastillas de leche at the PCC Processing Plant. In one month of plant exposure, he was able to put into application his knowledge on the nature of milk and its processing techniques. The internship also developed his industrial working and inter-personal skills. The proponent was also able to provide a plant profile and agency description; technical analysis on the practices and processing observed during the internship period; and recommendations to improved identified problems.